Phenolic composition and encapsulation of Brazilian grape seed extracts: evaluating color stabilizing capacity in grape juices - Elis Tatiane da Silva Nogueira
The color of grape juice is an important acceptance attribute by consumers, but it suffers losses during storage. The use of commercial antioxidants has limitations because the concept of a (3z(B100% natural drink(3y (Bof Brazilian legislation. This work characterized Brazilian grape seeds, and the cultivar extract with the greatest potential was encapsulated in arabic-gum (encapsulated extract-EE) to evaluate the color stabilizing capacity. The EE used in the grape juice was compared with the commercial antioxidants sulphite and enological tannin during storage (150 days). The BRS Magna and BRS Violeta grape seeds had the highest phenolic content, and the EE showed high catechin (4108 mg/kg), epicatechin (1161 mg/kg) and procyanidin-B2 (905 mg/kg) values. Sulfite was found to be the best color stabilizer. The use of EE (0.5 g/L) in grape juice improved color stability and anthocyanin stability. It was demonstrated that encapsulated grape seed extract has color stabilizing potential and that Brazilian grape seeds are a raw material of high technological value.s